Features of the apoptosis markers expression by skin cell with ageing - T. Yu. Vitruk; N. V. Ryazantseva; P. N. Pesterev; L. R. Mustafina (Бюллетень сибирской медицины, 2008)
The immunohistochemical study of skin was conducted to verify presence of p53, bcl-2 and bax apoptosis markers in epidermal keratinocytes of patients from two age groups: 16 to 44 years old and 45 to 64 years old. It was discovered that with chronological ageing of skin the expression levels of p53 and bax apoptosis markers are raised by epidermal cells in patients of elder age group. Obtained data testifies to cumulative damaging effect of a quantity of proapoptotic factors (oxidative stress, UV-waves, ionizing radiation, chemical reagents etc.) on epidermal cells with ageing.